2015
DOI: 10.7243/2055-7205-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Empirical comparisons of malpractice claims of different medical specialties

Abstract: Background: Variables affecting malpractice rates are important to the medical profession. Empirical data on trends in malpractice payments and settlements from anesthesiologists, surgeons, pediatricians and psychiatrists over an eight-year period are publicly available for analysis. Methods: A literature search of PubMed and Index Medicus was conducted for the years from 1985 to 2013 using the search terms National Practitioner Data Bank, physicians, and malpractice. Data from the National Practitioner Data B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Hence we accept the null hypothesis and maintain that there is no significant relationship between gross claims paid and gross premiums received in the Nigerian insurance industry. This is in line with studies carried out by Chandra, Nundy and Seabury (2005) and Reich and Schatzberg (2015) where they discovered that premiums charged by insurers are influenced by factors that have nothing to do with claims paid out. Similarly, a regression coefficient of -9339.65 indicates a negative and an indirect relationship between the variables.…”
Section: Regression Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…Hence we accept the null hypothesis and maintain that there is no significant relationship between gross claims paid and gross premiums received in the Nigerian insurance industry. This is in line with studies carried out by Chandra, Nundy and Seabury (2005) and Reich and Schatzberg (2015) where they discovered that premiums charged by insurers are influenced by factors that have nothing to do with claims paid out. Similarly, a regression coefficient of -9339.65 indicates a negative and an indirect relationship between the variables.…”
Section: Regression Analysissupporting
confidence: 89%
“…This is in line with the research conducted by Ramos (2017) and Fiedler (2018). Chandra, Nundy and Seabury (2005) in Reich and Schatzberg (2015) found that premiums charged by malpractice insurers may be influenced by factors that have nothing to do with claims paid out. They point out that the decline in insurer's investment income may be influenced by such non-medical factors like interest rates and premiums charged.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Use of the NPDB for research examining discipline or specialty specific outcomes is challenging. The NPDB does not identify provider specialty with sufficient precision to make unqualified statements about individual provider types (Reich & Schatzberg, 2015). NPDB reports constitute only those actions where a payment has been made, including those actions where a judgment was made in the favor of the provider or when a claimant settled a claim.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other specialties, psychiatrists are at an increased risk of disciplinary action, 11 with patient death by suicide as the number one cause of malpractice lawsuits against psychiatrists 12 . At any point in their clinical years, 68% of psychiatrists and 28% of psychologists have lost at least one patient due to suicide, with a third of all patient deaths by suicide occurring within 3 months of discharge from an inpatient psychiatric unit 13 .…”
Section: Resultsmentioning
confidence: 99%